2009
DOI: 10.1063/1.3081143
|View full text |Cite
|
Sign up to set email alerts
|

Building a polarizable pair interaction potential for lanthanoids(III) in liquid water: A molecular dynamics study of structure and dynamics of the whole series

Abstract: In this work we have extended our previously presented polarizable pair interaction potential for La(3+)-water [Duvail et al., J. Chem. Phys. 127, 034503 (2007)] to the whole lanthanoid(III) series (Ln(3+)) interacting with water. This was performed taking into account known modification of ionic radius and atomic polarizability across the series and thus changing potential parameters according to that. Our procedure avoids the hard task of doing expensive high level ab initio calculations for all the atoms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
155
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 96 publications
(192 citation statements)
references
References 56 publications
37
155
0
Order By: Relevance
“…2). Duvail et al reported the ADF peak values of 70 degree and 137 degree for La(III) [22] and 74 degree and 143 degree for Lu(III) [27], and these values compare well with ours in Fig. 5.…”
Section: Methodssupporting
confidence: 90%
See 4 more Smart Citations
“…2). Duvail et al reported the ADF peak values of 70 degree and 137 degree for La(III) [22] and 74 degree and 143 degree for Lu(III) [27], and these values compare well with ours in Fig. 5.…”
Section: Methodssupporting
confidence: 90%
“…These observations are in line with the RDF results (Fig. 4), again indicating that the gadolinium break [8][9][10][11][12] is not a sudden but smooth change in the hydrations of intermediate Ln(III) [24,27]. …”
Section: Methodssupporting
confidence: 89%
See 3 more Smart Citations